The Nomological Model of Study-Life Balance in Thai University Students - Chotratanakamol, Krisana; Bhanthumnavin, Duangduen Lekhyananda; Bhanthumnavin, Duchduen Emma; Meekun, Kosol; Pimthong, Saran; Kleebbua, Chaiyut (The Journal of Behavioral Science, 2023)
The pursuit of study-life balance (SLB) is a vital determinant of university students' overall success and well-being in academic and personal domains. However, there is still limited research currently available to bridge the empirical gap. This study aimed to investigate the direct and indirect effects of psychological characteristics and situational factors on study-life balance and sustainable success among Thai university students. The samples were 597 Thai university students, with an average age of 20 years old. Path analysis approach was used to analyze the data. The adjusted model indicated a good fit (χ2 = 39.086; df = 27; p-value = 0.0622; RMSEA = 0.027; CFI = 0.998; TLI = 0.995; SRMR = 0.050). The results showed that psychological traits construct and situational construct had both direct and indirect effects on SLB via psychological states construct, which explained 96.8% of the variance in SLB. Moreover, psychological states construct had a direct influence on sustainable success, and an indirect influence via SLB, which together explained 94.8% of the variance in sustainable success. The study identified psychological immunity, perceived opportunities for support from others, and proactive personality as important factors affecting SLB and sustainable success. The study highlights the significance of SLB for the success of Thai students. The findings shed light on the development of education courses or class activities based on the important factors outlined in this study to enhance SLB among Thai university students.